Atomistic mechanism of η'-to-η transformation in Al-Zn-Mg-Cu alloys. (1st July 2023) - Zhang, Xingpu; Wang, Jiangwei
Abstract: The atomistic mechanism of η'-to-η transformation in aged Al-Zn-Mg-Cu alloys has been investigated by using high-angle annular dark-field scanning transmission electron microscopy and density functional theory calculations. The η'-to-η transformation is accomplished by the structure transition from the orthorhombic units into the rhombohedral units, where the outward diffusion of selective Zn atoms, shear in (111)Al plane and also the shuffle of certain atoms are involved. The interaction between vacancy and η' is found to be able to assist the outward diffusion of Zn atoms and thus facilitate η'-to-η transformation. Via tuning the vacancy behaviours, a strategy to retard the coarsening of η' is proposed, which would benefit the design of high-performance Al alloys toward application in harsh conditions. Graphical abstract: Image, graphical abstract